Key Metabolic Pathways in MSC-Mediated Immunomodulation: Implications for the Prophylaxis and Treatment of Graft Versus Host Disease - Burnham, Andre J.; Foppiani, Elisabetta Manuela; Horwitz, Edwin M. (Frontiers in Immunology, 2020)
Mesenchymal stromal cells (MSCs) are spindle-shaped, plastic-adherent cells in vitro with potent immunosuppressive activity both in vitro and in vivo. MSCs have been employed as a cellular immunotherapy in diverse preclinical models and clinical trials, but most commonly as agents for the prophylaxis or therapy of graft versus host disease after hematopoietic cell transplantation. In addition to the oft studied secreted cytokines, several metabolic pathways intrinsic to MSCs, notably indoleamine 2,3-dioxygenase, prostaglandin E2, hypoxia-inducible factor 1 α, heme oxygenase-1, as well as energy-generating metabolism, have been shown to play roles in the immunomodulatory activity of MSCs. In this review, we discuss these key metabolic pathways in MSCs which have been reported to contribute to MSC therapeutic effects in the setting of hematopoietic cell transplantation and graft versus host disease. Understanding the contribution of MSC metabolism to immunomodulatory activity may substantially inform the development of future clinical applications of MSCs.